Serum IgG2 antibody multi-composition in systemic lupus erythematosus and in lupus nephritis (Part 2): prospective study. (22nd December 2020) - Bruschi, Maurizio; Moroni, Gabriella; Sinico, Renato Alberto; Franceschini, Franco; Fredi, Micaela; Vaglio, Augusto; Cavagna, Lorenzo; Petretto, Andrea; Pratesi, Federico; Migliorini, Paola; Locatelli, Francesco; Pazzola, Giulia; et al.
Abstract: Objectives: Circulating anti-ENO1 and anti-H2A IgG2 have been identified as specific signatures of LN in a cross-over approach. We sought to show whether the same antibodies identify selected population of patients with LN with potentially different clinical outcomes. Methods: Here we report the prospective analysis over 36 months of circulating IgG2 levels in patients with newly diagnosed LN ( n =91) and SLE ( n =31) and in other patients with SLE recruited within 2 years from diagnosis ( n =99). Anti-podocyte (ENO1), anti-nucleosome (DNA, histone 2 A, histone 3) and anti-circulating proteins (C1q, AnnexinA1-ANXA1) IgG2 antibodies were determined by home-made techniques. Results: LN patients were the main focus of the study. Anti-ENO1, anti-H2A and anti-ANXA1 IgG2 decreased in parallel to proteinuria and normalized within 12 months in the majority of patients while anti-dsDNA IgG2 remained high over the 36 months. Anti-ENO1 and anti-H2A had the highest association with proteinuria (Heat Map) and identified the highest number of patients with high proteinuria (68% and 71% respectively) and/or with reduced estimated glomerula filtration rate (eGFR) (58% for both antibodies) compared with 23% and 17% of anti-dsDNA (agreement analysis). Anti-ENO1 positive LN patients had higher proteinuria than negative patients at T 0 and presented the maximal decrement within 12 months. Conclusions: Anti-ENO1, anti-H2A and anti-ANXA1 antibodies were associated with high proteinuria in LN patients and Anti-ENO1 also presented the maximal reduction within 12 months that paralleled the decrease of proteinuria. Anti-dsDNA were not associated with renal outcome parameters. New IgG2 antibody signatures should be utilized as tracers of personalized therapies in LN. Trial registration: The Zeus study was registered at https://clinicaltrials.gov (study number: NCT02403115).